ROBUST METHOD TO DEFINE AN OPTIMUM LEVEL OF AN AIR TRAFFIC CONTROLLER SIMULATOR TRAINING - Lazorenko, Vitalii; Kharchenko, Volodymyr (Proceedings of National Aviation University (archive), 2018)
Purpose: to set optimum level of preparation and to structure the process of trainee preparation, as well as to analyze outcomes for ATC instructor. Methods: we have chosen to define an optimum level of preparation are Robust, mean square and mean median methods. The most reliable method to protect our data from outliers is Robust method. Results: to manage the position of outcomes we forced to structure specific filtering tasks which are mandatory to be done by trainee, in order to guaranty not exceeding predefined level of preparation. To satisfy our goal we have also predefined media tools to apply, such as: Part Task Trainer, Other Training Devises, Radar Trainer, Automated Work Place ‘Situation’. Discussion: professional preparation of an air traffic controller is a very complicated and time-consuming process with many specialists and instructors been involved. Preparation process roughly divided into the part of theoretical knowledge obtaining and the part where trainees are practicing to convert theoretical material into practical skills with the help of Simulator. For the interim check, common criteria of skill acquisition process is predefined by evaluation of technological operations: Acceptance of duty on the work place, Phraseology adequacy, Coordination with adjacent units, Regularity of flights, Accuracy of aircraft’s positions determination, Correspondence of decision making to given situation, Provision of proper separation and general Safety issues, Adequacy of console operations. Instructor evaluates trainee on all his activities, beginning from trainee’s readiness of task execution ending by feedback analysis and provision of further recommendations. Completeness, adequacy and quality of mentioned above results depend in direct on quality of instructor.